KAJIAN PEMANFAATAN LIMBAH PADAT INDUSTRI PENGOLAHAN AGARAGAR KERTAS BERBAHAN BAKU RUMPUT LAUT Gracilaria sp. SEBAGAI PUPUK PADA TANAMAN BAYAM (Amaranthus sp.) - Adiguna, Galih S.; Pramesti, Rini; Susanto, A. B. (977-2407769)
Study the utilization of solid waste seaweed Gracilaria sp. processing results agar paper as fertilizer on plant spinach (Amaranthus sp .) has been done. Case studies in Agar-Agar Paper Factory Cap Apples in the Village Mancagahar, Pamengpeuk District, Garut regency. Was comparing parameters with seaweed solid waste compost on the market and testing this on the test plant spinach (Amaranthus sp .). Results of chemical analysis of seaweed solid waste generated from agar paper processing is pH 7.3 (neutral), COrganic 27.28 %; moisture content 29.98 % ; ratio C / N 8, N-total 3.42 % ; Phosphorus 0.37%, Ca 10.44%, Mg 0.98 %, 1.54 % K, 1.70% Na; 2573 ppm Fe; 5 ppm Cu; 182 ppm Zn; Mn 83 ppm; KTK 49.33 cmol / kg; KB> 100%. These results meet the minimum technical requirements of organic fertilizer. Optimal results on plant growth test using the media of waste, waste treatment that achieved by 15% , while the use of compost to be achieved in compost treatment 25%. Solid waste of seaweed has the potential as spinach (Amaranthus sp .) plant fertilizer.